Nonnegative solutions to superlinear problems of generalized Gelfand type. (1995) - O'Regan, Donal
Abstract : Existence of nonnegative solutions to superlinear second order problems of the form y ″ + μ q ( t ) g ( t, y ) is discussed in this paper. Here μ ≥ 0 is a parameter.